Nanodiamond-containing polyethyleneimine hybrid materials for lead adsorption from aqueous media - KAHRAMAN, MEMET VEZİR; AYDIN URUCU, OYA (WILEY, 2019)
This study describes the preparation of new surface-modified nanodiamond (ND) particles containing urethane-based hybrid materials by photopolymerization of aliphatic urethane acrylate, trimethylolpropane triacrylate, glycidyl methacrylate monomers, and their usage for lead adsorption from aqueous media. ND and synthesized surface-modified ND were characterized by atom transfer radical addition Fourier transform infrared spectroscopy (ATR-FTIR) and scanning transmission electron microscopy analysis. Crosslinked adsorbent nanocomposites were then treated with polyethylene imine and all adsorbent nanocomposites were characterized by ATR-FTIR, scanning electron microscopy, thermogravimetric analysis, and contact angle measurements. The metal ion binding capacity of the surfaces of the nanocomposites containing high amine content was investigated. The effects of the percentage of functional monomer, pH, and contact time on adsorption, and the interaction of foreign metal ions have been tested. Optimum contact time was found to be 7 h at pH 5. The adsorption capacity of the synthesized nanocomposite adsorbent for lead (II) was determined as 17.12 mg g(-1). Langmuir and Freundlich isotherms were used to determine the adsorption behaviors and Langmuir isotherm model was found to be the most suitable model (R-2: 0.9988). The amount of adsorption of Pb (II) ions of UV curable adsorbent film prepared in river water samples was investigated. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48241.
Keywords: adsorbent; lead; nanodiamond; photograft; photopolymerization; polyethyleneimine; HEAVY-METAL IONS; THERMAL-PROPERTIES; ACTIVATED CARBON; COMPOSITE; REMOVAL; SURFACE; NANOPARTICLES; PERFORMANCE; ADSORBENT; PARTICLES